THE PORTRAYAL OF INDONESIAN WOMEN IN TABLOID WANITA INDONESIA:LA MARXIST FEMINIST ANALYSIS IN "CERMIN" COLUMNS OF TABLOID WANITA INDONESIA IN 2007 - Eka Purnawati, - (2009)
The research entitled The Portrayal of Indonesian Women in Tabloid Wanita Indonesia discusses the contemporary reality of Indonesian women based on tabloid Wanita Indonesia. It claims itself as a tabloid or weekly magazine especially for women. The writer employs the existence of mass media as the subject of study in order to see a glance of contemporary reality of Indonesian women because she considers that mass media of women puts an imperative concern in providing information about women in all aspects, however, it can not be assumed that this tabloid represents Indonesian women entirely. The writer writes the research paper after being inspired by the condition of Indonesian women that is represented and depicted in tabloid Wanita Indonesia. The writer believes that this research will give a contribution to the writer's future in order to be a journalist. The study employs a qualitative descriptive method, in which the lists of figures, characteristics, education, and careers as the instruments used for collecting the data. Thus, the data are analyzed through the framework of Marxist Feminist perspective in order to observe the portrayal of Indonesian women existed in tabloid Wanita Indonesia. The findings reveal the portrayals of Indonesian women as women who get equal opportunities and rights in contributing and participating in all spheres. Indonesian women are depicted as educated persons and economically independent because they work outside the household. They are not only successful in taking care of their families but also their businesses or their jobs. Thus, Indonesian women are not regarded as weak, subordinate and unintelligent people because they could prove that in public sectors women can do as good as what men can. The writer expects that this research is not only able to enrich our understanding in literature but also to give a new perspective of women's existence in whole aspects of their life; intellectual, social, cultural, political and economic aspects that can be contributed to entire society especially to women's community.